Proceedings of the 2nd International Conference on Data Engineering and Communication Technology ICDECT 2017 - Kulkarni, Anand J.; Satapathy, Suresh Chandra; Kang, Tai; Kashan, Ali Husseinzadeh (Advances in Intelligent Systems and Computing, 2019)
This book features research work presented at the 2nd International Conference on Data Engineering and Communication Technology (ICDECT) held on December 15-16, 2017 at Symbiosis International University, Pune, Maharashtra, India. It discusses advanced, multi-disciplinary research into smart computing, information systems and electronic systems, focusing on innovation paradigms in system knowledge, intelligence and sustainability that can be applied to provide feasible solutions to varied problems in society, the environment and industry. It also addresses the deployment of emerging computational and knowledge transfer approaches, optimizing solutions in a variety of disciplines of computer science and electronics engineering.